FRI0028 In vitro inhibitory effect of etanercept on autophagy: a new mechanism of action of tnf inhibitors in rheumatoid arthritis. (15th June 2017) - Vomero, M; Capozzi, A; Barbati, C; Colasanti, T; Manganelli, V; Ceccarelli, F; Spinelli, FR; Conti, F; Perricone, C; Finucci, A; Pendolino, M; Scrivo, R; et al.
Abstract : Background: Autophagy has emerged as a key mechanism in the development, survival and function of immune cells and dysregulation of autophagic pathway has been implicated in the pathogenesis of several autoimmune diseases including Rheumatoid Arthritis (RA) (1). In fact, autophagy seems to be involved in the generation of citrullinated peptides, with consequent breakage of tolerance in RA (2). Moreover, increased autophagy levels and a reduction of apoptosis-related molecules have been found in RA synovial tissues and a role of TNF-induced autophagy in RA development has been proposed (3). Objectives: The aim of the study was to analysed the effect of TNF and anti-TNF inhibitor etanercept on autophagy and apoptosis in cells involved in RA pathogenesis. Methods: Peripheral blood mononuclear cells (PBMCs) and fibroblast-like synoviocytes (FLS) isolated from RA patients were cultured in presence of TNF and in serum deprivation state (starvation) for 4 hours and then etanercept, at concentration of 15 ug/mL, were added to the culture. After 24h cells were analyzed for levels of autophagy marker LC3-II by western blot and for percentage of annexin V-positive apoptotic cells by flow cytometry. Results: As expected, TNF and starvation induced autophagy on RA PBMC and FLS in dose-dependent manner after 24h of culture (p<0.05 in all experimental conditions). Moreover, the adding of etanercept caused a significant reduction of LC3-II levels (p=0.004) and an increase of apoptosis rate (p=0.002) after both pro-autophagic stimuli (p<0.05). Conclusions: We demonstrated for the first time an inhibitory effect of etanercept on autophagy activation of cells involved in RA pathogenesis. In addition, our findings suggest a crucial role of autophagy in RA cells survival. References: Pierdominici M, Vomero M, Barbati C et al. Role of autophagy in immunity and autoimmunity, with a special focus on systemic lupus erythematosus. FASEB J. 2012; 26:1400–12. Sorice M, Iannuccelli C, Manganelli V et al. Autophagy generates citrullinated peptides in human synoviocytes: a possible trigger for anti-citrullinated peptide antibodies. Rheumatology. 2016;55:1374–85. Rockel JS, Kapoor M. Autophagy: controlling cell fate in rheumatic diseases. Nat Rev Rheumatol. 2016;12:517–31. Disclosure of Interest: None declared